تحليل محتوى كتاب الرياضيات للصف الرابع الإبتدائي بالمملكة العربية السعودية وفقا لمتطلبات دراسة التوجهات الدولية للرياضيات والعلوم TIMSS - بدر، بثينة بنت محمد بن محمود (جامعة الكويت - مجلس النشر العلمي, 2016)
هدفت الدراسة إلى تحليل محتوى كتاب الرياضيات للصف الرابع الابتدائي بالمملكة العربية السعودية وفقاً لمتطلبات دراسة التوجهات الدولية للرياضيات والعلوم (TIMSS). استخدمت الباحثة المنهج الوصفي التحليلي، وذلك للوقوف على الخصائص العامة لكتاب الرياضيات للصف الرابع الابتدائي بالمملكة العربية السعودية (الفصل الأول – الفصل الثاني). وتم اختيار مجتمع الدراسة من كافة الموضوعات المتضمنة بمحتوى كتابي الرياضيات (الفصل الأول – الفصل الثاني) للصف الرابع الابتدائي من منهاج الرياضيات للعام الدراسي (1433-1434ه). لتحقيق ذلك قامت الباحثة بإعداد قائمة بمتطلبات (TIMSS-2011) الواجب تضمنها بمحتوى كتاب الرياضيات للصف الرابع الابتدائي. وأداة تحليل المحتوى لكتاب الرياضيات للصف الرابع الابتدائي وفق متطلبات (TIMSS-2011). وخلصت الدراسة إلى عدم توافر التوزيع المناسب طبقاً لمتطلبات TIMSS-2011 للخصائص العامة لكتاب الرياضيات للصف الرابع الابتدائي بالمملكة العربية السعودية.
The study aims to analyze the content of the developed Mathematics book of the fourth primary grade of Saudi Arabia in accordance with the requirements of the study of International trends for Mathematics and Science (TIMSS). The researcher used the descriptive analytical method in order to determine the general characteristics of the developed Mathematics book of the fourth primary grade of Saudi Arabia (Term I - Term II) requirements (TIMSS-2011). The sample was selected from all subjects included in the math book (Term I - Term II) for the fourth grade of primary mathematics curriculum for the academic year (1433-1434 AH). The researcher prepared a list of requirements (TIMSS-2011) to be included in the content of the mathematics books for fourth grade primary. The study indicated that the lack of appropriate distribution in accordance with the requirements of the TIMSS-2011 for the general characteristics of the developed Mathematics book of the fourth primary grade of Saudi Arabia.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- علم الرياضيات -- التعليم الإبتدائي -- طلاب المرحلة الإبتدائية